A review of COVID-19-associated mucormycosis in India - Khadke, Sumanth; Khadke, Vidhatri; Tomar, Shubham; Khanuja, Purvi K.; Suresh, Surya; Sohail, Muhammad R.; Khanna, Arjun (International Journal Of Community Medicine And Public Health, 2022)
The resurgence of COVID-19 with the delta variant has accompanied a doubling in the prevalence of COVID-19-associated mucormycosis (CAM) in India. The prevalence grew to 80 times that of the global average. In this review, we describe the epidemiology, the clinical presentation, and treatment of CAM. We conducted a literature search on the PubMed, Google Scholar, Embase, and Harvard Library databases. The cytokine storm with high interleukin-6 (IL-6), hyperglycemia, ketoacidosis culminates into impaired endothelial and immune response, causing improved survival of the fungus. The most common presentation is rhinoorbital cerebral mucormycosis followed by pulmonary mucormycosis in patients with COVID-19. CAM patients have active or prior pulmonary tuberculosis, hyperglycemia, or a prolonged stay in the intensive care unit (ICU). A recent history of steroid medications and a high prevalence of tuberculosis (TB) may have contributed to an increased prevalence of CAM infections. Hypoxemic COVID-19 patients have a substantial improvement with steroid treatment but increases the risk of opportunistic infections. Although radiological signs have been described but the most common presentation is a subtle sign of eye, nasal, oral cavity, or pulmonary symptoms which requires high index of suspicion. Hence, one should not rely on radiological signs alone. Amphotericin B or isavuconazole along with surgical debridement is the treatment of choice for CAM. Early admission, diagnosis, and treatment lead to favorable outcomes.